Intelligent Natural Language Processing: Trends and Applications - Shaalan, Khaled; Hassanien, Aboul Ella.; Tolba, Fahmy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book brings together scientists, researchers, practitioners, and students from academia and industry to present recent and ongoing research activities concerning the latest advances, techniques, and applications of natural language processing systems, and to promote the exchange of new ideas and lessons learned. Taken together, the chapters of this book provide a collection of high-quality research works that address broad challenges in both theoretical and applied aspects of intelligent natural language processing. The book presents the state-of-the-art in research on natural language processing, computational linguistics, applied Arabic linguistics and related areas. New trends in natural language processing systems are rapidly emerging - and finding application in various domains including education, travel and tourism, and healthcare, among others. Many issues encountered during the development of these applications can be resolved by incorporating language technology solutions. The topics covered by the book include: Character and Speech Recognition; Morphological, Syntactic, and Semantic Processing; Information Extraction; Information Retrieval and Question Answering; Text Classification and Text Mining; Text Summarization; Sentiment Analysis; Machine Translation Building and Evaluating Linguistic Resources; and Intelligent Language Tutoring Systems.
Keywords: Computational intelligence; Natural language processing (Computer science).; Computational linguistics; Big data; Computational Intelligence; Natural Language Processing (NLP).; Computational Linguistics; Big Data